Fluvial-tidal to fluvial-lacustrine sedimentation of the Middle Miocene to Pleistocene mapia formation, Dogiyai, Papua (Indonesia) - Fakhruddin, Rakhmat (Penerbit Universiti Kebangsaan Malaysia, 2021)
A sedimentological and palynological investigation was carried out on outcropping sedimentary rocks at Dogiyai, Papua, proposed to be named as the Mapia Formation. The age range is from Middle Miocene to Pleistocene. The lower Mapia Formation was deposited at Metroxylon type to Nothofagus emarcida Zone, Middle Miocene to Early Pliocene. It is comprised of three facies associations: tidal channel, tidal point bar, and tidal flat deposits. A tidally dominated fluvially influenced depositional environment is suggested for the deposition of sediments of this unit. The upper Mapia Formation was deposited at Malvacipollis diversus Zone, Garcinia cuspidata type Zone, and Proteacidites sp. Zone, Late Pliocene to Pleistocene. It is comprised of five facies associations: delta front, slump, debrite, turbidite, and lacustrine mud deposits. A non-channelized deep-lacustrine slump and debris-flow dominated depositional environment is suggested for the deposition of sediments of this unit. The lower Mapia Formation was deposited as synorogenic clastic sediments at the beginning of Central Range orogeny event while the upper Mapia Formation was deposited in the piggyback basin at the major uplift event.